The Practice of Muhallil Marriage for a Wife who Has been Divorced Three Times According to the Perspective of Islamic Law in North Kuripan Community, West Lombok District - Haeratun; Ita Surayya; Jamaluddin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Marriage essentially aims to form a household that is Sakinah Mawaddah, Warohmah and must be registered at the KUA (religious affairs office) to be recognized by the state, but this tahlil marriage is not registered at the religious affairs. KUA office is only carried out with the intention of divorcing her after having biological relationship. He is not intended to form a family. Under such conditions, it is necessary to disseminate information to the public, especially regarding the practice of muhalil marriage in accordance with Islamic law. The activity methods are lectures, discussions, and questions and also answer. The results of this activity can be concluded that there is still a lack of knowledge and insight in the community regarding marriage so that this activity can help the community.